REVIEW: RANDOMIZED CLINICAL TRIAL STUDY OF INFLUENZA VACCINE IN CHILDREN AGE 6-35 MONTHS - Cecep Suhandi; Cheryl Alodya; Abednego Kristande; Rano Kurnia Sinuraya (Universitas Islam Indonesia, 2022)
Background: Influenza is a contagious viral infection disease that causes acute disorders of the respiratory tract. The prevalence of infection due to influenza virus is higher in children than adults. Thus, it is very important to vaccinate children using the most effective type of vaccine.Objectives: The purpose of this review was to investigate type of influenza vaccine with the highest effectiveness in children 6 to 35 months of age based on RCT study.Methods: The review is carried out by collecting articles from Elsevier and Medline database using “.Influenza Vaccine”, “Randomized Control Trial”, and “Children” as the keywords.Results: Based on the initial searching, it was found 6.261 articles and 9 articles that fulfill the review criteria. The results showed that the best vaccine efficacy has gotten by trivalent vaccines against the strains of viruses A (H1N1), A (H3N2), and B (Yamagata) with vaccine efficacy values of 94.1%; 100%; and 97.1%, respectively. While the use of quadrivalent vaccines against strain B (Victoria) virus with a vaccine efficacy value of 87.2%.Conclusions: Trivalent vaccine more effective for strain A and B (Yamagata) virus, moreover quadrivalent vaccine more effective for strain B (Victoria)Keywords: Influenza, vaccine, children, trivalent, quadrivalent Intisari Latar Belakang: Influenza merupakan suatu penyakit infeksi virus menular yang mengakibatkan gangguan akut pada saluran pernapasan. Insidensi infeksi akibat virus influenza lebih tinggi terjadi pada anak-anak dibanding dewasa. Dengan demikian, sangat penting untuk memberikan vaksinasi pada anak-anak menggunakan jenis vaksin yang paling efektif. Tujuan: Tujuan dari review ini adalah untuk menentukan jenis vaksin influenza dengan efektivitas tertinggi terhadap anak usia 6-35 bulan berdasarkan hasil studi (RCT).Metode: Review dilakukan dengan penelusuran pustaka pada database ELSEVIER dan MEDLINE dengan kata kunci “Influenza Vaccine”, “Randomized Control Trial”, dan “Children”.Hasil: Berdasarkan hasil penelusuran, diperoleh 6.261 artikel dan 9 artikel yang memenuhi kriteria review. Hasil telaah dapat menunjukkan bahwa efektivitas vaksin terbaik pada vaksin trivalent terhadap virus strain A (H1N1), A (H3N2), dan B (Yamagata) dengan nilai efikasi vaksin secara berurutan sebesar 94,1%; 100%; dan 97,1% untuk usia anak 12-35 bulan. Sedangkan penggunaan vaksin quadrivalent terhadap virus strain B (Victoria) dapat mencapai nilai efikasi vaksin 87,2% pada anak usia 6-35 bulan. Kesimpulan: Vaksin trivalent lebih efektif pada virus strain A dan B (Yamagata), sedangkan vaksin quadrivalent lebih efektif pada strain B (Victoria)Kata kunci: Influenza, vaksin, anak-anak, trivalent, quadrivalent